2007
DOI: 10.11646/zootaxa.1462.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The genera of the Neotropical armored catfish subfamily Loricariinae  (Siluriformes: Loricariidae): a practical key and synopsis

Abstract: The subfamily Loricariinae belongs to the Neotropical mailed catfish family Loricariidae. Members of Loricariinae are recognized by their long and flattened caudal peduncle and absence of an adipose fin. Despite important studies conducted on this group, no comprehensive generic key is presently available. A Hill & Smith (1976) analysis and cluster analysis were performed on external morphological characters taken from specimens or borrowed from the literature. The two main groups recognized correspond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 28 publications
1
64
0
8
Order By: Relevance
“…Within the latter, they redefined the subtribes Loricariina and Farlowellina (incorrectly named Sturisomina in Covain et al , 2008; corrected in Covain et al , 2010). Covain et al (2008) furthermore demonstrated that the characteristics of the mouth and the caudal fin are autocorrelated with the phylogeny and that they are sufficient to define tribal and subtribal ranks, as well as several of the morphological groups proposed in Covain & Fisch‐Muller (2007).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Within the latter, they redefined the subtribes Loricariina and Farlowellina (incorrectly named Sturisomina in Covain et al , 2008; corrected in Covain et al , 2010). Covain et al (2008) furthermore demonstrated that the characteristics of the mouth and the caudal fin are autocorrelated with the phylogeny and that they are sufficient to define tribal and subtribal ranks, as well as several of the morphological groups proposed in Covain & Fisch‐Muller (2007).…”
Section: Introductionmentioning
confidence: 96%
“…Within the Loricariidae, members of the subfamily Loricariinae are united by a long and depressed caudal peduncle and by the absence of an adipose fin, but they exhibit substantial variation in body shape, lip morphology and dentition. There are currently 220 valid species of Loricariinae, distributed in 30 genera (Covain & Fisch‐Muller, 2007; Fichberg & Chamon, 2008; Ghazzi, 2008; Ingenito et al , 2008; Rapp Py‐Daniel & Fichberg, 2008; Rodriguez & Miquelarena, 2008; Rodriguez & Reis, 2008; Rodriguez et al , 2008; Thomas & Rapp Py‐Daniel, 2008; de Carvalho Paixão & Toledo‐Piza, 2009; Thomas & Sabaj Pérez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Its depressed body (dorsal-ventrally flattened) covered by bony plates reduces water resistance (Geerinckx et al 2007), while the mouth structures shaped into a sucker disc allow individuals to adhere to submerged rocks (Covain & Fisch-Muller 2007). The partial redundancy analysis exhibited interesting relations between species occurrence and environmental gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Identification to species level follows Isbrücker and Nijssen (1976) and Covain and Fisch-Muller (2007) based on the following characters: lower lip bilobate with median furrow; whip on upper caudal spine absent; abdomen covered with small plates lacking organisation; elliptical area of abdominal plates at level of pelvic girdle absent; rostrum not strongly pronounced; pelvic-fin spine longer than last pelvic-fin branched ray; colouration comprising dark dots (except ventral surface and anal fin); lower lobe of caudal darker than upper; and basicaudal spot present in juveniles.…”
Section: Checklistsmentioning
confidence: 99%